Mathematical literacy and learning styles: A study on student geometry learning - Alma, Alma Saputri; Rochaminah, Sutji Rochaminah; Ismaimuza, Dasa Ismaimuza; Fajriani (Desimal: Jurnal Matematika, 2025)
This study aims to analyze students' mathematical literacy in solving geometry problems reviewed from learning styles. This type of research is descriptive research. The approach used in this study is a qualitative approach. Data collection techniques include learning style questionnaires, written tests, and interviews. The credibility of the data in this study uses time triangulation. The data was analyzed descriptively to describe the results of students' mathematical literacy tests. The results of the study show that 1) students with visual learning styles in mathematics literacy are at level 2, because they are only able to solve level 1 and level 2 mathematics literacy problems, visual students have difficulty in solving mathematics literacy problems at a higher level; 2) Students with an auditory learning style in mathematical literacy are at level 4, able to do a more in-depth analysis when solving math literacy problems from level 1 to level 4, but have difficulty solving problems in levels 5 and 6; 3) Students with kinesthetic learning styles in mathematics literacy are only at level 1; kinesthetic students have great difficulty in solving mathematics literacy problems at a higher level.